2014
DOI: 10.1039/c3nj01430d
|View full text |Cite
|
Sign up to set email alerts
|

A structure–property relationship study of bent-core mesogens with pyridine as the central unit

Abstract: The synthesis and characterization of pyridine bent-core liquid crystals are reported. Some compounds exhibit B1 and B7 mesophases. Lower and wider mesophase ranges are obtained by decreasing the polarity of linkers between the pyridine ring and the inner aromatic rings, and increasing the length of terminal chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The liquid crystal properties of the synthesized compounds were studied using POM, DSC, and XRD and compared with those of the unsubstituted parent compound (Fig. 17), which was reported by Marković et al 107 Studies revealed that on introducing the methoxy group, the mesogenic properties were quenched and the melting point decreased (110 C) compared to that of the parent compound. On the other hand, enantiotropic B1-like phase was observed in the chloroand nitro-substituted compounds.…”
Section: Pyridine-based Bent-shaped Mesogensmentioning
confidence: 83%
See 1 more Smart Citation
“…The liquid crystal properties of the synthesized compounds were studied using POM, DSC, and XRD and compared with those of the unsubstituted parent compound (Fig. 17), which was reported by Marković et al 107 Studies revealed that on introducing the methoxy group, the mesogenic properties were quenched and the melting point decreased (110 C) compared to that of the parent compound. On the other hand, enantiotropic B1-like phase was observed in the chloroand nitro-substituted compounds.…”
Section: Pyridine-based Bent-shaped Mesogensmentioning
confidence: 83%
“…4-(2-(trans-4-n-Propylcyclohexyl)ethyl)iodobenzene (108) was synthesized as described in a previous report by Chen et al, 50,51 and organic dye 117 was synthesized by referring to a previous report by Wu et al 52 2-Methylbut-3-yn-2-ol (106) in triethylamine (Et 3 N) was then, DCM was added to it, and the organic layer was washed using saturated ammonium chloride solution and dried using anhydrous MgSO 4 . Later, the solvents were evaporated to yield 2-methyl-4-(pyridin-4-yl)but-3-yn-2-ol (107). A mixture of KOH, acetylenic alcohol 107, and TBAB in PhMe/H 2 O at a ratio of 4 : 1 (v/v) was stirred for 30 min at 60 C under nitrogen protection.…”
Section: Pyridine-based Molecules As Thermotropic Mesogensmentioning
confidence: 99%
“…This feature opens up opportunities for obtaining photoactive materials with high quantum efficiency as well as good charge transporting ability. A number of pyridine-based mesogens has been reported in the literature, including rod-like molecules [1][2][3][4][5][6] , bent-shaped molecules with up to five aromatic rings [7][8][9][10][11][12][13] and polymers [14][15][16] .Their mesogenic properties may be attributed to the enhanced unsaturation and polarizability caused by the presence of this heteroaromatic ring 8 . Non-mesogenic pyridine derivatives have been used in mixtures with non-mesogenic carboxylic acids to lead to hydrogen-bonded complexes, which arrange to form different mesophases [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that, in bent-core mesogens with pyridine at the central ring the mesophase range becomes lower and wider as the polarity of the bent-core is decreased by changing the linking group from amide to ester and to olefinic 9 . In continuation of our work, here we present the synthesis and characterization of a series of five-phenyl ring containing bentcore compounds (B5), where we have substituted the hydrogen atomat the peripheral phenyl rings of the bent core B5-Hbearing the olefinic linking group between the central pyridine ring and wings (Figure 1a) 9 , with substituents X. In the synthesized compounds the substituent X varies as: B5-MeO (X = CH 3 O), B5-Cl (X = Cl) and B5-NO 2 (X = NO 2 ) (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation